Partisipasi Perempuan Indonesia dalam Politik: Participation Of Indonesianwomen In Politics - Wardah Hayati (An-Nisa’ Journal of Gender Studies, 2009)
Indonesian women still have a long way to go in fighting for their representation in political institutions. To date, the representation of women in legislative bodies remains very low compared to the female population. This article explores the importance of women's involvement in politics, the issues they face, and efforts to increase their participation. Masih memerlukan perjuangan yang panjang bagi wanita Indonesia untuk memperjuangkan keterwakilan mereka di lembaga-lembaga politik Sampai saat ini keterwakilan perempuan di lembaga legislatif masih sangat kecil jika dibanding jumlah populasi perempuan. Artikel ini dimaksudkan untuk menelusuri pentingnya keterlibatan perempuan di bidang politik, masalah-masalah yang dihadapi dan upaya untuk meningkatkan partisipasi mereka.